An Evaluation of Students’ Effective (ESL) Acquisition through ICT in Nigeria - Irewole, Michael Olayinka (NIU Journal of Humanities; Vol 4 No 1 (2019): KIU Journal of Humanities, Vol. 4 No. 1, March 2019, 2019)
The contemporary teaching and learning processes of languages in general and English Language in particular are characterized by a host of innovations and manipulations. The integration of digital media helps in developing a favourable attitude and impetus of students towards English Language acquisition being a foreign language. This paper therefore examined an evaluation of students’ effective ESL acquisition through ICT in Nigeria. A number of methods have been employed to solve the problem of lack of proper acquisition of English Language as a Second Language in Nigeria. This is due to the status ascribed to English Language as a lingual franca which serves as medium of communication used in ministries and parastatals. It is also the medium of instruction in Nigerian schools. This has called for acquisition of additional language, especially in a classroom context which is not an easy task and takes a long time. It is viewed by (Pulido, 2007) that the cognitive and linguistics processes involved in language acquisition are complex. That is, the learner of another language is already an adult who has been used to the grammar/syntax, phonology and the vocabulary of his L1. It may be difficult for this learner to reconcile the differences between his L1 and the new/target language to acquire. It was on this note that this study investigates the ICT and its attendance impact on the students’ effective acquisition of Second Language in some selected secondary schools in Ekiti State, Nigeria. The population comprises the Senior Secondary School 2 students in Ekiti State. Two groups of schools were selected. The first group was subjected to the use of ICT for teaching and learning of English Language while the other group used conventional methods. Four schools were randomly selected as sampling technique for equal representation. A total of 400 students formed the sample size for the study. The results of the two groups were analyzed using ex-post-factor design. The result of the finding showed that using ICT facilities in Nigerian secondary schools have a significant impact in acquisition of L2. It also revealed that the use of ICT create an alternative and easy access to linguistic facilities apart from the classroom’s teaching learning process for effective acquisition of second language.